The source of atmospheric aerosols in inland Antarctica (abstract) - Kanamori, Satoru; Kanamori, Nobuko; Nishikawa, Masataka; Watanabe, Okitsugu; Aoki, Shuhji; Iwasaka, Yasu-nobu; Nishio, Fumihiko; Okada, Kikuo (National Institute of Polar Research, 1993)
P(論文) Extensive sampling of drifting snow and pit snow were carried out on Mizuho Plateau by JARE-29 along the route from near the sea shore (point S20) up to about 600km inland (point A). The typical sea salt components, Na and Cl, in summer drifting snow are high near the coast and decrease exponentially inland. In contrast, n. s. s. SO_4 and NO_3 show abrupt rises at most inland, suggesting that they are supplied from high altitude. The compositions of atmospheric aerosols and drifting or surface snow show a considerable positive correlation and, therefore, the chemical composition of atmospheric aerosols in the past can be traced back from that in deposited snow with time mark from departmental bulletin paper